Influence of Organic Additives for Zinc-Air Batteries on Cathode Stability and Performance - Kube, Alexander; Wagner, Norbert; Friedrich, K. Andreas (Journal of The Electrochemical Society, 2021)
In this work, a theoretically predicted electrolyte composition comprising 6 M potassium hydroxide (KOH), 2 M citric acid, 1 M glycine, and 0.5 M zinc oxide is tested in terms of electrochemical performance, cathode stability, and electrolyte stability. It is shown that dissolved metal ions from the cathode reacted with the introduced organic additives, reduced the cathode stability, and blocked metal oxidation reactions. This was due to a Kolbe-like decomposition reaction that occurred because of the presence of potassium citrate, which formed because of the reaction of KOH and citric acid. Furthermore, intermediate products of this decomposition reaction appeared to block the cathode's surface, hindering oxygen (O2) evolution and reducing the overall cell performance. The decomposition of potassium citrate starts above 1.7 V Zn. Additionally, it is shown that tribase citric acid behaves similarly to a dibase carbonic acid. Both decrease the onset potential for the O2 reduction reaction from 0.9 V vs reversible hydrogen electrode (RHE) for pure 6 M KOH to 0.6 V vs RHE for KOH with these organic acids.